Histopathological Aspects as Predictor of Recurrency of Locally Advanced Breast Cancer - Rizki, Kiki Akhmad; Djajakusumah, Teguh Marfen; Agustina, Hasrayati; Hidayat, Peri (Majalah Kedokteran Bandung, 2024)
The histopathological aspect of breast cancer has been established as one of the important prognostic factors of recurrence. This study aimed to determine whether histopathological examination can be used as a predictor of the incidence of recurrence in locally advanced breast cancer patients. This was a cohort retrospective observational study with a correlative analytical approach. Subjects of this study were breast cancer patients who have undergone mastectomy and/or received additional therapy at Dr. Hasan Sadikin General Hospital Bandung, Indonesia, between January 2017 and September 2019. Data were collected through medical records and anatomical histopathology data. Subjects were divided based on their recurrency status. A total of 62 breast cancer patients were included in the study with 31 recurrent patients and 31 non-recurrent patients. A total of 29 patients in the recurrent group (93.5%) had lymphovascular invasion. Histopathology grading showed a difference in both groups, in which recurrent group patients were mostly (74.2%) in the high histopathological grade while 51.6% of samples in non-recurrent group were categorized as moderate histopathological grade. Complete histopathological margins were found in both recurrent and non-recurrent groups for 54.8% and 87.1% respectively. There is a correlation between histopathologic grading, lymphovascular invasion, and incision margin with the recurrence of a locally advanced stage breast cancer. It can be concluded that some histopathological aspects can be used as a predictor of recurrence in locally advanced breast cancer.